Estimation of the effectiveness of surgical treatment of patients with old rupture of heel tendon with short plaster splint immobilization - N. S. Ponomarenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Heel tendon injuries is the most common trauma of tendomuscular apparatus. Old ruptures of heel tendon occur in 58 % of cases in humans. The aim of the research was to estimate the effectiveness of treatment of the patients with old ruptures of heel tendon with Myerson type III defects who had tendon reconstruction on Chernavsky and short plaster splint immobilization of lower extremity for 4 weeks. We operated 10 patients using reconstruction on Chernavsky in our clinic from 2012 to 2014 (average age - 47,6 ± 12,0 years, 8 males and 2 females). All patients had old ruptures of heel tendon. Average time from the moment of trauma till the operation was 112,6 ± 80,4 days. Diastasis between the ends of tendon was 5,8 ± 0,7 cm that corresponds to Myerson type 111. Average term of staying at hospital was 10 ± 2 days. We didn't register any complications in postoperative period. Term of plaster immobilization of the operated extremity was 4 weeks. AOFAS score was 34,2 ± 6,8 points at the control examination in 1,5 months that corresponds to bad functional result. We registered good functional results (88,6 ± 3,5 points) in 3 months. 1n 6 months, functional results were 95,9 ± 1,6 points. 1n 12 months after the operation average score was 97,9 ± 2,1 points that corresponds to excellent functional result. Using heel tendon reconstruction on Chernavsky at the Myerson type 111 defects in combination with short plaster immobilization and early activization of patients allows to decrease term of rehabilitation of patients after the operation.